(Opportunities) Death of Newspaper Industry in Digital Age and Covid-19 Pandemic - Supadiyanto, Supadiyanto (Jurnal The Messenger, 2020)
Newspaper industry is entering a state of emergency in Indonesia. Dewan Pers demands that the government provide incentives to press companies during Covid-19. The growth in the number of internet users, the downward trend in advertising revenue, and the number of newspaper circulation are problems in the print media business. List of questions in this study: what are the trends in the use of internet technology and social media in Indonesia?; why did various newspaper companies in Indonesia collapse and die in the digital era?; how is the effort to save the newspaper business? Meanwhile, the research paradigm is qualitative. The time of the study is November 2019 to May 2020. The results of this research, the growth in the number of internet users has been extraordinary in the last 20 years. Signs of the newspaper era are over, strengthened by many newspaper companies turning to online media. The number of readers fell, the number of advertisers plummeted, number of copies narrowed, and the cost of producing newspapers became increasingly expensive to cause the closure of various newspaper companies. Rescue by attracting young readers and doing various innovations. Tragically, the print media industry will end and die on its own.